Pengaruh Profitabilitas, Opini Audit, Ukuran Perusahaan terhadap Audit Delay dengan Good Corporate Governance Sebagai Variable Moderating - Mohammad Fajar Ruddin; Suwarno Suwarno (Universitas Muhammadiyah Gresik, 2022)
This study aims to test Profitability, Audit Opinion, Firm Size on Audit Delay and the moderating role of Good Corporate Governance (GCG). The method of collecting data is purposive sampling on companies listed on the Indonesia Stock Exchange platform for the period 2018-2020. Profitability was tested using the ratio of return on assets, while good corporate governance was measured using the ASEAN CG Scorecard. The results showed that profitability had an effect on audit delay and good corporate governance was able to moderate this relationship significantly. However, firm size and audit opinion have no effect on audit delay and good corporate governance is not able to moderate this relationship.